Pharmacogenomics of Vincristine‐Induced Peripheral Neuropathy Implicates Pharmacokinetic and Inherited Neuropathy Genes - Wright, Galen E.B. (Clin Pharmacol Ther, 2018)
Vincristine is an effective chemotherapeutic drug for various cancers, including acute lymphoblastic leukemia (ALL). Unfortunately, clinical utility is restricted by dose‐limiting vincristine‐induced peripheral neuropathies (VIPN). We sought to determine the association of VIPN with a recently identified risk variant, CEP72 rs924607, and drug absorption, distribution, metabolism, and excretion (ADME) gene variants in pediatric ALL. This was followed by a meta‐analysis of pharmacogenomic data from over 500 patients. CEP72 rs924607 was significantly associated with VIPN (P = 0.02; odds ratio (OR) = 3.4). ADME analyses identified associations between VIPN and ABCC1 rs3784867 (P = 5.34 × 10(−5); OR = 4.9), and SLC5A7 rs1013940 (P = 9.00 × 10(−4); OR= 8.6); genes involved in vincristine transport and inherited neuropathies, respectively. Meta‐analysis identified an association with a variant related to TTPA (rs10504361: P = 6.85 × 10(−4); OR = 2.0), a heritable neuropathy‐related gene. This study provides essential corroboratory evidence for CEP72 rs924607 and highlights the importance of drug transporter and inherited neuropathy genes in VIPN.